2014
DOI: 10.3390/antib3020192
|View full text |Cite
|
Sign up to set email alerts
|

Role of B Cells in Breaking and Maintaining Tolerance to Clotting Factor VIII in Congenital and Acquired Hemophilia A

Abstract: Immune responses directed against clotting factor FVIII (FVIII) seriously complicate treatments for patients with hemophilia A. This response can manifest in congenital hemophilia A patients who generate inhibitor antibodies that bind and inactivate -transplanted‖ replacement FVIII, as well as in acquired hemophiliacs, whose immune systems have lost tolerance to self-FVIII. Regardless of the mechanism by which production of anti-FVIII inhibitor antibody is triggered, the maintenance of this deleterious respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Several clinical and experimental studies have shown that B cells are key in maintaining and breaking tolerance to FVIII. 13 In fact, the production of neutralizing Abs relies on the development FVIII specific memory B cells or long-lived plasma cells, on one hand, while generation of several distinct regulatory cells may prevent inhibitor formation on the other hand, as evidenced in animal models using anti-CD3 monoclonal antibody therapy. 14 In this study, we explored whether these newly identified Breg cells might play a role, with other cells, in the development of neutralizing Abs in patients with hemophilia A. Interestingly, our findings showed that levels of circulating Breg cells were significantly reduced in hemophilia A patients with inhibitors compared to patients without inhibitors or healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and experimental studies have shown that B cells are key in maintaining and breaking tolerance to FVIII. 13 In fact, the production of neutralizing Abs relies on the development FVIII specific memory B cells or long-lived plasma cells, on one hand, while generation of several distinct regulatory cells may prevent inhibitor formation on the other hand, as evidenced in animal models using anti-CD3 monoclonal antibody therapy. 14 In this study, we explored whether these newly identified Breg cells might play a role, with other cells, in the development of neutralizing Abs in patients with hemophilia A. Interestingly, our findings showed that levels of circulating Breg cells were significantly reduced in hemophilia A patients with inhibitors compared to patients without inhibitors or healthy controls.…”
Section: Discussionmentioning
confidence: 99%